2011
DOI: 10.1038/bjc.2011.257
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib and dacarbazine as first-line therapy for advanced melanoma: phase I and open-label phase II studies

Abstract: Method:The safety of oral sorafenib up to a maximum protocol-specified dose combined with dacarbazine in patients with metastatic, histologically confirmed melanoma was investigated in a phase I dose-escalation study and the activity of the combination was explored in an open-label phase II study.Results:In the phase I study, three patients were treated with sorafenib 200 mg twice daily (b.i.d.) plus 1000 mg m−2 dacarbazine on day 1 of a 21-day cycle and 15 patients had the sorafenib dose escalated to 400 mg b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 35 publications
0
23
1
Order By: Relevance
“…Sorafenib and sunitinib are multi-tyrosine kinase inhibitors that aim to downregulate neoangiogenesis via inhibition of multiple molecular pathways. To our knowledge, there are seven published trials assessing their efficacy in patients with metastatic melanoma (Table 2) [39][40][41][42][43][44][45]. Five out of the seven trials allowed patients with BM to participate.…”
Section: Reviewmentioning
confidence: 99%
“…Sorafenib and sunitinib are multi-tyrosine kinase inhibitors that aim to downregulate neoangiogenesis via inhibition of multiple molecular pathways. To our knowledge, there are seven published trials assessing their efficacy in patients with metastatic melanoma (Table 2) [39][40][41][42][43][44][45]. Five out of the seven trials allowed patients with BM to participate.…”
Section: Reviewmentioning
confidence: 99%
“…It has been shown that use of sorafenib enhances the response of melanoma to regional chemotherapy (Augustine et al 2010). Anti-cancer activity of sorafenib in malignant melanomas has been demonstrated in several studies (Eisen et al 2011;Escudier et al 2007). Among the latest inhibitors of the aberrant BRAF activity is a synthetic compound PLX4032 (vemurafenib).…”
Section: Braf Gene Mutation V600ementioning
confidence: 99%
“…Common genetic mutations Cutaneous BRAF ~ 50% [Davies et al 2002;Cheng et al 2011;Long et al 2011] V600E 80% V600K 16% V600G/R 3% NRAS 20% [Goel et al 2006;Jakob et al 2011] Acral/mucosal c-KIT 10% [Curtin et al 2006;Jiang et al 2008] BRAF/NRAS <10% [Wong et al 2005] Uveal GNAQ ~ 45% [Onken et al 2008;Van Raamsdonk et al 2010] GNA11 ~ 60% [Onken et al 2008;Van Raamsdonk et al 2010] frequent grade 2 and higher adverse events (AEs) associated with vemurafenib were arthralgia (21%), rash (18%), fatigue (13%), alopecia (8%), photosensitivity (12%), nausea (8%) and diarrhoea (5% [Eisen et al 2011;Hauschild et al 2009;McDermott et al 2008]. RAF-265 is another small-molecule multikinase inhibitor of mutant/wild-type BRAF and VEGFR.…”
Section: Melanoma Typementioning
confidence: 99%